IMPLEMENTASI HONEYPOT PADA JARINGAN INTERNET LABOR FAKULTAS TEKNIK UNIKS MENGGUNAKAN DIONAEA SEBAGAI KEAMANAN JARINGAN - Rosi Dermawati; Muhammad Hasim Siregar (Universitas Trunojoyo Madura, 2020)
AbstractLack of knowladge of computer user about system security problem is one of the cause of computer problems. There are many computers that do not update their antivirus and some even do not use an antivirus. Network security techniques usually block attacks using a firewall or detect attack with IDS (Intruction Detection System), which is in charge of guarding against axisting attacks. However, by only using IDS the network administrator will be overwhelmed checking every notification given by IDS. This IDS works almost the same as an antivirus, unable to work in an encrypted environment or an IPv6 environment. For that, additional security is needed such as a dionaea honeypot. A honeypot is a fake system the signed to trap attacker, as if it were a real system. Based on these problems, a research will be conducted on the Analysis And Implementation Of Honeypot Using Dionaea as Network Security Support. Keywords: Honeypot, Dionaea, IDS, Firewall, Malware